Kuntowijoyo's Perspective Prophetic Education Concept and Its Implementation in Aqidah Moral Subjects - Wilam Nafilah Robaeah; Tatang Muh Nasir; Dadang Komara; Eneng Dewi Siti Sobariah; Hidayat Aji Permana (Ta'dib, 2024)
This research aims to determine the concept of Prophetic Education from Kuntowijoyo's perspective, its implementation, as well as supporting and inhibiting factors in the implementation of Prophetic Education in the Aqidah Moral subjects at MA Miftahul 'Ulum Purwakarta. This research focuses on the application of Kuntowijoyo's prophetic education in Akidah Akhlak lessons at MA, using a qualitative approach with data collection techniques such as interviews, observation and documentation. Data analysis was carried out through the stages of data reduction, data presentation and data verification. The results of this research show that according to Kuntowijoyo, prophetic social science has three main components, namely amar ma'ruf (humanization), nahi munkar (liberation), and iman billah (transcendence) within the framework of the Al-Qur'an, Surah Ali-Imran verse 110. The implementation of prophetic education is reflected in the learning objectives, learning materials, and learning evaluation in the Aqidah Moral subjects. Supporting factors in implementing prophetic education include the important role of educators and the availability of adequate facilities and infrastructure. Meanwhile, the obstacles faced include a lack of role models from teaching staff in madrasas and inadequate supervision of students.